A systematic review on the association of the G8 with geriatric assessment, prognosis and course of treatment in older patients with cancer. Issue 6 (November 2019) - van Walree, Inez Charlotte; Scheepers, Ellen; van Huis-Tanja, Lieke; Emmelot-Vonk, Marielle H.; Bellera, Carine; Soubeyran, Pierre; Hamaker, Marije E.
Abstract: Aim: The aim of this systematic review is to summarise all available data on the use of the G8 screening tool in geriatric oncology, focusing on the diagnostic accuracy of the G8 to predict the presence of impairments on geriatric assessment (GA) and on its association with different clinical outcomes (survival, course of treatment and patient-centred outcomes). Methods: A systematic search in MEDLINE and EMBASE for studies on the use of the G8 in older patients with cancer. Results: The literature search identified 8987 reports, of which 54 publications from 46 studies were included (including 18 conference abstracts). 19 studies compared the diagnostic characteristics of the G8 with GA. Median sensitivity and specificity of the G8 for frailty on GA were respectively: 85% and 64%. Out of the 24 studies addressing the association of the G8 with survival, 15 (63%) found the G8 was associated with survival. Six out of fourteen studies (43%) reporting on treatment-related complications found an association between G8 scores and risk of complications. Treatment completion, health care utilisation and patient-centred outcomes were investigated less frequently. Conclusion: The G8 is a useful diagnostic tool to identify older patients with cancer who require full GA and is associated with survival and treatment-related complications. Future prospective studies should investigate whether the G8 is predictive for other relevant clinical outcomes such as treatment completion and patient-centred outcomes.